Combining classical molecular dynamics and quantum mechanical methods for the description of electronic excitations: The case of carotenoids. Issue 11 (8th January 2016) - Prandi, Ingrid G.; Viani, Lucas; Andreussi, Oliviero; Mennucci, Benedetta
Abstract : Carotenoids are important actors both in light‐harvesting (LH) and in photoprotection functions of photosynthetic pigment–protein complexes. A deep theoretical investigation of this multiple role is still missing owing to the difficulty of describing the delicate interplay between electronic and nuclear degrees of freedom. A possible strategy is to combine accurate quantum mechanical (QM) methods with classical molecular dynamics. To do this, however, accurate force–fields (FF) are necessary. This article presents a new FF for the different carotenoids present in LH complexes of plants. The results show that all the important structural properties described by the new FF are in very good agreement with QM reference values. This increased accuracy in the simulation of the structural fluctuations is also reflected in the description of excited states. Both the energy order and the different nature of the lowest singlet states are preserved during the dynamics when the new FF is used, whereas an unphysical mixing is found when a standard FF is used. © 2016 Wiley Periodicals, Inc. Abstract : An effective strategy is presented to describe the structural effects on electronic excitations of carotenoids by combining specifically parameterized force field and TDDFT calculations. The important structural properties described by the new force field are in very good agreement with quantum mechanical reference values. This increased accuracy in the simulation of the structural fluctuations is also reflected in the description of excited states.